The Influence Of Organizational Culture And Job Satisfaction On Organizational Commitment (Hermina Hospital Case Study) - Masriana Damanik; Muhammad Isa Indrawan (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to determine and analyze the influence of Organizational Culture and Job Satisfaction on Organizational Commitment at Hermina Hospital. This type of research used is Quantitative and Associative. The population in this study amounted to 150 employees and the sample used was the Slovin formula. After the sample was withdrawn, the results for a sample were 109 employees. The data source used was primary data using questionnaires as an instrument for data collection and using survey methods. This study uses a multiple linear analysis model for statistical analysis and the regression model has been tested beforehand in the classical assumption test. The results of the partial t-test study show that organizational culture has a positive and significant effect on organizational commitment and job satisfaction. It also has a positive and significant effect on organizational commitment. The results of the f test also show that organizational culture and job satisfaction have a positive and significant effect on organizational commitment at Hermina Hospital.